Financial markets appetite for risk: and the challenge of assessing its evolution by risk appetite indicators - Birgit Uhlenbrock (Deutsche Bundesbank, 2009)
Assessments of investors' risk appetite/aversion stance via indicators often yields results which seem unsatisfactory (see e.g. Illing and Aaron (2005)). Understanding how such indicators work therefore seems essential for further improvements. The present paper seeks to contribute to this evolution, focusing on the Global Risk Appetite Index (GRAI) class of indicators going back to Kumar and Persaud (2002). Looking at international stock indices during the subprime crisis in 2007, the plausibility of the GRAIs benefits from applying the rank correlation approach of Kumar and Persaud (2002) combined with a modified version of the factor-transformation extension proposed by Misina (2006).
Keywords: G11; G12; G15; 330; Risk appetite indicators; risk aversion indicators; asset pricing; financial markets.; Risikopräferenz; Anlageverhalten; Index; Indexberechnung; Börsenkurs; Aktienindex; Internationaler Finanzmarkt; Finanzmarktkrise; Börsenkrise; Welt